1998
DOI: 10.1038/sj.bmt.1701140
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus viridans bacteremia following autologous peripheral blood stem cell transplantation

Abstract: Summary:A retrospective evaluation of 200 consecutive recipients of autologous peripheral blood stem cell transplantation was conducted to ascertain the incidence and outcome of Streptococcus viridans bacteremia as well as to determine the role of prophylactic ampicillin therapy in the peri-transplant setting. Viridans streptococci were isolated from the blood of 35 individuals at a median of 6 days (range 2-8 days) following stem cell infusion. The most common isolates were S. sanguis and S. mitis. All patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 26 publications
2
21
1
Order By: Relevance
“…When the incidence of positive blood cultures was evaluated in patients with OM and those ones who did not present OM in GA and GB, it was also observed that there was no statistically significant differences in the Groups. This data was contrary to data presented by other studies quoting OM as a cause of the bacteremia (1,(13)(14)(15)(16). It is worth mentioning that out of 19 (26%) positive blood cultures in 73 patients, only 1 (1.36%) was positive for α-hemolytic viridans streptococci (Streptococcus intermedius) and that happened in a patient from GB, who did not presented OM.…”
Section: Discussioncontrasting
confidence: 55%
“…When the incidence of positive blood cultures was evaluated in patients with OM and those ones who did not present OM in GA and GB, it was also observed that there was no statistically significant differences in the Groups. This data was contrary to data presented by other studies quoting OM as a cause of the bacteremia (1,(13)(14)(15)(16). It is worth mentioning that out of 19 (26%) positive blood cultures in 73 patients, only 1 (1.36%) was positive for α-hemolytic viridans streptococci (Streptococcus intermedius) and that happened in a patient from GB, who did not presented OM.…”
Section: Discussioncontrasting
confidence: 55%
“…Importantly, viridans group streptococcal bacteremia may be complicated by hypotension, septic shock, and adult respiratory distress syndrome, which have a high mortality rate (5,7,18,29). Oral penicillin V or roxythromycin added to a fluoroquinolone have resulted in significant reductions of viridans group streptococcal bacteremia (20,22).…”
mentioning
confidence: 99%
“…Gram-positive coccal bacteremia is a common adverse event associated with PBSC transplantation and was also encountered in our series. 27 From this limited experience, it was unclear whether prior splenectomy affected the risk of bacteremia in our patients. CMV reactivation, as encountered in patient 005, is not uncommon following autologous PBSC transplantation.…”
Section: Discussionmentioning
confidence: 99%